Evaluación de la oportunidad de desarrollo de las mipymes del sub-sector confecciones: a propósito de la firma del TLC con EE. UU. - Pinto Castro, Jose (2009)
This article presents research conclusions about how the Free Trade Agreement with USA could impact the micro and small clothes makers’ finance. Furthermore, it presents the results of a survey among a group of micro and small clothes makers from Gamarra Street.